Response of Westerly Jet Over the Northern Hemisphere to Astronomical Insolation During the Holocene - Zhou, Peng; Shi, Zhengguo; Li, Xinzhou; Zhou, Weijian (Frontiers in Earth Science, 2020)
The westerly jet (WJ) in the upper troposphere, an important atmospheric circulation system, is critical for influencing global climate by changes of its north-south migration and intensity. However, its variations during the Holocene across the Eurasian and North America are not well evaluated, which restricts our understanding of climate change in those regions. Using general circulation model experiments, here we simulate the variations of WJ over the past 10ka to show its intensity and position of WJ responding to astronomical insolation. Our results suggest that the summer WJ gradually migrates southward and strengthens over the Central Asia, Japan and North America from the early to late Holocene; meanwhile, the positions of the winter WJ barely move and its intensity slightly change. These seasonally asymmetric changes can be attributed to the temperature structure, in which the surface latent and sensible heat flux both contribute.